PERANCANGAN DAN ANALISIS INTEGRASI HYPERSONIC WAVERIDER–INLET SCRAMJET (DESIGN AND ANALYSIS OF HYPERSONIC WAVERIDER– SCRAMJET INLET INTEGRATION) - Malik, Deden Ridwan; Bura, Romie Oktovianus (BRIN Publishing, 2014)
Nowadays, several hypersonic vehicle designs have existed and waverider is one of them. Waverider has been introduced for more than 50 years yet only a few have been operated. This is due to several difficulties in design processes dan propulsion system integration. The present research was conducted by designing general wedgederived waverider and integrating it with scramjet inlet. The waverider design process is based on one-dimensional flowfield analysis, while the scramjet inlet integration is based on exergy analysis. Through this investigation, a design variable – Exergy Destruction Rate (EDR) - would be obtained to correlate the waverider design with the integration of scramjet inlet